"Making the alliance even greater": (Mis-)managing U.S.-Japan relations in the age of Trump. Issue 2 (4th May 2021) - O'Shea, Paul; Maslow, Sebastian
ABSTRACT: President Donald Trump's "America First" policy questions the fundamentals of the global U.S.-led alliance network. Where other allies implemented hedging strategies, Japan's Prime Minister Abe Shinzō pledged to "make the alliance even greater, " insisting that the bilateral ties were "airtight" and "stronger than ever before." However, Trump's approach to trade, détente with North Korea, and off-the-cuff remarks regarding nuclear weapons invigorated criticism in Japan: the U.S. is an unreliable partner and Japan needs to prepare for life after the alliance. We argue that Abe's embrace of Trump was successful in staving off the worst, maintaining stability at the cost of personal humiliation and certain trade and security interests. However, Trump's cavalier treatment of Japan has laid bare the realities of the alliance, potentially revitalizing a more autonomous discourse of alternatives to the current and often "humiliating" modus in alliance management.